Soft Diplomacy SBY dalam Konflik Indonesia-Malaysia: Studi Kebijakan SBY terhadap Pelanggaran Kedaulatan oleh Malaysia di Perairan Bintan Tahun 2010 - Mohamad Rosyidin (Jurnal Kajian Wilayah, 2014)
This paper seeks to interpret and evaluate President Yudhoyonos diplomatic approach towards Malaysia regarding the captured of three Indonesian officials in 2010 by Malaysian Maritime Police. It is interesting since violation of state sovereignty had triggered mass protest in Indonesia, the executive ignored the public demand. Rather than using coercive approach, the Indonesian elite employed soft diplomacy to engage Malaysia towards win-win solutions. This paper argues that Yudhoyonos foreign policy towards Malaysia in this context is counterproductive to increase nations self-esteem. Yudhoyonos soft diplomacy only matters for short term interest but not for long term one. This paper argues that the strategy chosen by President Yudhoyono is rooted from his misconception of soft power. This paper also suggest that soft power alone is insufficient to serve national interest; it need to be combine with hard power. As such, the effective diplomacy is smart power; the combination of soft and hard power which is compatible to the Second Principle of Pancasila.Keywords: soft diplomacy, soft power, SBYs foreign policy, smart power